Transcriptional repression of GTL1 under water‐deficit stress promotes anthocyanin biosynthesis to enhance drought tolerance - Noel Anthony Mano; Mearaj A. Shaikh; Joshua R. Widhalm; Chan Yul Yoo; Michael V. Mickelbart (Plant Direct)
Abstract The transcription factor GT2‐LIKE 1 (GTL1) has been implicated in orchestrating a transcriptional network of diverse physiological, biochemical, and developmental processes. In response to water‐limiting conditions, GTL1 is a negative regulator of stomatal development, but its potential rolein other water‐deficit responses is unknown. We hypothesized that GTL1 regulates transcriptome changes associated with drought tolerance over leaf developmental stages. To test the hypothesis, gene expression was profiled by RNA‐seq analysis in emerging and expanding leaves of wild‐type and a drought‐tolerant gtl1‐4 knockout mutant under well‐watered and water‐deficit conditions. Our comparative analysis of genotype‐treatment combinations within leaf developmental age identified 459 and 1073 differentially expressed genes in emerging and expanding leaves, respectively, as water‐deficit responsive GTL1‐regulated genes. Transcriptional profiling identified a potential role of GTL1 in two important pathways previously linked to drought tolerance: flavonoid and polyamine biosynthesis. In expanding leaves, negative regulation of GTL1 under water‐deficit conditions promotes biosynthesis of flavonoids and anthocyanins that may contribute to drought tolerance. Quantification of polyamines did not support a role for GTL1 in these drought‐responsive pathways, but this is likely due to the complex nature of polyamine synthesis and turnover. Our global transcriptome analysis suggests that transcriptional repression of GTL1 by water deficit allows plants to activate diverse pathways that collectively contribute to drought tolerance.